Atypical non-progressive semantic impairment following allogeneic bone marrow transplantation in a patient with Waldenström's macroglobulinemia: A case report. Issue 4 (19th May 2019) - Zangrandi, Andrea; Gasparini, Federico; Imovilli, Annalisa; Napoli, Manuela; Marti, Alessandro; Angelini, Damiano; Barletta-Rodolfi, Caterina; Ghidoni, Enrico
Abstract: Objective: A case report of a 74-year-old male presenting with an atypical multimodal semantic impairment. The patient was diagnosed with Waldenström macroglobulinemia (WM) for which he received allogeneic bone marrow transplantation (BMT) due to disease progression. Following BMT, he developed a sudden onset of semantic difficulties that have remained unchanged for eight years. No other cognitive functions have been affected and his activities of daily living remain fully preserved. Method: The patient was assessed at our neuropsychology unit with six neuropsychological evaluations over an 8-years follow-up period following BMT. Additional semantic tests were administered during the last three evaluations. Four MRI scans (at age 62, 66, 69 and 74) and 18F-FDG PET (at age 74) were obtained. Results: The patient presents a multimodal semantic impairment, including naming impairment, visual agnosia, prosopoanomia, associative prosopagnosia, topographical disorientation and impaired retrograde memory for public events. MRI scans and 18F-FDG PET revealed bilateral symmetrical atrophy (temporal > frontal) and inferior bilateral temporal lobe hypometabolism, respectively. Neuroradiological examination was unremarkable prior to BMT. Conclusion: Clinical diagnosis remains a challenge given the focal and stable nature of his deficits. We hypothesize that the BMT procedure might have resulted in the temporal lobe damage and subsequent semantic impairment. We recommend obtaining a thorough neuropsychological evaluation of patients who receive allogenic BMT, both prior to and following transplant.